Fabrication of mechanically advanced polydopamine decorated hydroxyapatite/polyvinyl alcohol bio-composite for biomedical applications: In-vitro physicochemical and biological evaluation. (December 2022) - Erdem, Umit; Dogan, Deniz; Bozer, Busra M.; Turkoz, Mustafa B.; Yıldırım, Gurcan; Metin, Aysegul U.
Abstract: In this study, polydopamine (PDA) coated hydroxyapatite (HA) reinforced polyvinyl alcohol (PVA) films were produced to be used in biomedical applications such as bone tissue regeneration. pDA is coated not only to prevent the agglomeration of HA when encountering interstitial fluids but also to strongly bind the PVA for the interaction between materials so that the mechanical performance becomes more stabilized. pDA was coated on the hydroxyapatite surface using a radical polymerization technique, and the reinforced PVA were produced with pDA-coated HA (pDA-HA/PVA) nanoparticles. Fundamental characteristic properties of pDA-HA/PVA nanocomposite films were examined by morphological/chemical (SEM-EDS), microstructural (XRD, Ft-IR, and Raman), thermodynamic (TGA and TM), mechanical performance (Vickers microhardness) and biological activity analysis (MTT, genotoxicity and antimicrobial efficacy investigations). Physicochemical analysis showed that all the samples studied exhibited homogeneous mineral distributions through the main structures. According to TGA, TMA and hardness tests, the new composite structure possessed higher mechanical properties than neat PVA. Further, pDA-HA/PVA nanocomposites exhibited high antibacterial capacities against Acinetobacter Baumannii (A.Baumannii), Staphylococcus aureus ( S. aureus ), and Streptococcus mutans (S.mutans). Moreover, the new nanocomposites were noted to present good biocompatibility for fibroblast (L929) cells and to support remarkably MCS cells. All in all, this comprehensive work shows that the thermo-mechanically improved pDA-HA/PVA films will increase the application fields of PVA in biomedical fields especially tooth-bone treatments for coating, filling, or occlusion purposes. Graphical abstract: Image 1 Highlights: pDA-HA/PVA membrane is a suitable carrier membrane with its thermal and mechanical stabilities. The use of pDA offered strong interfacial adhesion and high mechanical properties. Addition of HA improved the biocompatibility and antimicrobial properties of biocomposite.